Individual Differences among Grapheme-Color Synesthetes: Brain-Behavior Correlations - Hubbard, Edward M.; Arman, A. Cyrus; Ramachandran, Vilayanur S.; Boynton, Geoffrey M. (Neuron (Cambridge, Mass.), 2005)
Grapheme-color synesthetes experience specific colors associated with specific number or letter characters. To determine the neural locus of this condition, we compared behavioral and fMRI responses in six grapheme-color synesthetes to control subjects. In our behavioral experiments, we found that a subject’s synesthetic experience can aid in texture segregation (experiment 1) and reduce the effects of crowding (experiment 2). For synesthetes, graphemes produced larger fMRI responses in color-selective area human V4 than for control subjects (experiment 3). Importantly, we found a correlation within subjects between the behavioral and fMRI results; subjects with better performance on the behavioral experiments showed larger fMRI responses in early retinotopic visual areas (V1, V2, V3, and hV4). These results suggest that grapheme-color synesthesia is the result of cross-activation between grapheme-selective and color-selective brain areas. The correlation between the behavioral and fMRI results suggests that grapheme-color synesthetes may constitute a heterogeneous group.